Old State House at 206 Washington Street, ca. 1895 - Stebbins, Nathaniel L. (Tufts Archival Research Center, 2005)
Street-level view west-southwest of the Old State House, located at 206 Washington Street. A balcony, statues and clock adorn the east elevation of the Old State House. A street lamp is attached to the southeast corner of the building. 17 State Street is included along the left side of the photograph. The Sears Building, located at the corner of Washington and Court Streets, is visible in the background of the photograph. Pedestrians and horse-drawn wagons fill the sidewalks and streets surrounding the Old State House. Photographs